Актуальні правові аспекти інформаційного забезпечення інноваційної діяльності - Подрез-Ряполова, І. В. (НДІ ПЗІР НАПрН України, 2022)
У науковій роботі досліджені окремі актуальні правові аспекти інформаційного забезпечення інноваційної діяльності. Підтверджено, що інформаційне забезпечення інноваційного процесу повинне бути направлено на створення ефективних засобів доступу до інформаційних ресурсів та оптимальне управління ними від започаткування ідеї до комерціалізації результатів інноваційної діяльності. У статті зроблений аналіз норм чинного положення Кабінету Міністрів України «Про Національну електронну науково-інформаційну систему», головною метою якої є збір, формування, збереження, верифікація даних та інформації у сфері наукової і науково-технічної діяльності, забезпечення доступу до них та використання, а також автоматизації процедур та процесів взаємодії суб’єктів та користувачів системи. Встановлено, що Національна електронна науково-інформаційна система функціонує на важливіших принципах науковості, гуманізму, демократії, органічного поєднання освітньої, наукової та інноваційної діяльності. Саме через реалізацію вказаних принципів, в тому числі принципу поєднання освітньої, наукової та інноваційної діяльності, можливе забезпечення сталого інноваційного розвитку національної економіки. Зазначено, що створення Ukrainian Research Information System є прикладом впровадження найкращих європейських та загальносвітових практик та має на меті стимулювання розвитку наукової, науково-технічної та інноваційної сфер. У роботі зроблено висновок щодо важливого значення функціонування розглянутої електронної науково-інформаційної системи для належного провадження наукової, науково-технічної, інноваційної діяльності та інфраструктурного забезпечення інноваційного процесу. Визначено, що ефективність інноваційної діяльності повинна забезпечуватися за допомогою відповідних ресурсів (в тому числі інформаційних) та визначатися саме рівнем відповідного інформаційного забезпечення. Problem setting. It should be agreed that the primary task of the organization of information provision of innovative activity is the formation of information resources, the composition of which should be oriented towards the establishment of information links between participants (subjects) of the innovation sphere, which carry out activities at all stages of the innovation process, in order to ensure mutual relations the connection between demand and supply of innovative products of national production. Moreover, information provision should be oriented towards the creation of effective means of access to information resources and their optimal management from the birth of an idea to the commercialization of the results of innovative activity. In today’s conditions, the issue of information support for innovative activities is gaining considerable relevance, taking into account modern trends in the introduction and use of the latest information technologies (resources). Analysis of recent researches and publications. The issue of ensuring the innovation process and innovative activity (including information) was considered in the works of many scientists. Thus, S.V. Hlibko considered the issue of functional support of the innovation process. The study of the technology transfer mechanism and its implementation in the innovation process was conducted by O.V. Rozghon.In addition, Yu. V. Pasmor considered the problems of information provision of innovations. However, today there is not a large number of scientific studies that would comprehensively cover the issue of information provision of innovative activities, therefore this topic is relevant and requires additional research. Target of the research is to study the current legal aspects of information support of the innovation process, including the study of issues of formation and use of information resources in the field of innovation activity. Article’s main body. In the scientific work, some relevant legal aspects of information provision of innovative activities are investigated. The article analyzes the norms of the current regulation of the Cabinet of Ministers of Ukraine «About the Ukrainian Research Information System», the main purpose of which is the collection, formation, preservation, verification of data and information in the field of scientific and scientific and technical activities, ensuring access to them and their use as well as automation of procedures and processes of interaction between subjects and users of the system. It has been established that the Ukrainian Research Information System functions on the more important principles of scientificity, humanism, democracy, organic combination of educational, scientific and innovative activities. It is through the implementation of the specified principles, including the principle of combining educational, scientific and innovative activities, that it is possible to ensure sustainable innovative development of the national economy. It is noted that the creation of the Ukrainian Research Information System is an example of the implementation of the best European and global practices and aims to stimulate the development of scientific, scientific and technical and innovative spheres. Conclusions and prospects for the development. As a result of consideration of current legal issues of information support of innovative activity, in particular the process of legislative implementation and the peculiarities of the functioning of the Ukrainian Research Information System, it is appropriate to draw a conclusion regarding the importance of this system for the proper implementation of scientific, scientific and technical, innovative activities and infrastructural support of the innovative process. In addition, it should be emphasized that the information infrastructure should ensure the formation and implementation of new information resources and appropriate access to them by users. Therefore, the main task of the process of organizing the information support of innovative activity should be the formation of innovative resources. That is, the effectiveness of innovative activity must be ensured with the help of appropriate resources (including information) and determined precisely by the level of appropriate information support. In addition, the development of scientific, scientific-technical and innovative activities requires the availability of a modern and up-to-date information base.
Keywords: інноваційна діяльність; інноваційний процес; інформаційне забезпечення; інформаційні ресурси; innovative activity; innovative process; information support; information resources